2020
DOI: 10.1186/s12914-020-00225-z
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health of women living with HIV in Muslim-majority countries: a systematic mixed studies review

Abstract: Background: The number of women living with the human immunodeficiency virus (WLHIV) in Muslim-majority countries has increased significantly in the last decade. These women are often marginalized and face insecure sexual and reproductive health (SRH) needs and rights. However, little is known about the multi-faceted factors influencing these women's fertility, contraceptive, and perinatal decisions and sexual life. This systematic mixed studies review aimed to synthesize the empirical evidence on social, cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 69 publications
(204 reference statements)
0
11
0
Order By: Relevance
“…Compared to developed countries, longstanding variations in human rights, socioeconomic conditions, public policies, and health systems in developing countries differentially restrict women from accessing quality health services, achieving sexual health, and making reproductive decisions [ 28 31 ], especially women infected with HIV [ 32 42 ]. In developing countries, WLH have less favorable and more varied conditions for sexual health and reproductive services than WLH in developed countries [ 43 – 46 ] due to a complex mixture of gender and disease associated inequities related to cultural norms [ 47 ], religious doctrines [ 48 ], poverty [ 49 ], health policy [ 50 ], health services [ 51 ], and emergency conditions [ 52 ]. Developed countries provide WLH with the most supportive environments for sexual health and to engage in reproductive decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to developed countries, longstanding variations in human rights, socioeconomic conditions, public policies, and health systems in developing countries differentially restrict women from accessing quality health services, achieving sexual health, and making reproductive decisions [ 28 31 ], especially women infected with HIV [ 32 42 ]. In developing countries, WLH have less favorable and more varied conditions for sexual health and reproductive services than WLH in developed countries [ 43 – 46 ] due to a complex mixture of gender and disease associated inequities related to cultural norms [ 47 ], religious doctrines [ 48 ], poverty [ 49 ], health policy [ 50 ], health services [ 51 ], and emergency conditions [ 52 ]. Developed countries provide WLH with the most supportive environments for sexual health and to engage in reproductive decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…32 Unsatisfactory sexual life post-HIV diagnosis has been reported in a review in Muslimmajority countries, which similarly found the reasons were related to ART event, HIV status denial, and fear of transmitting the infection. 9,15 The present study also linked the sexual dissatisfaction with women's anger and disappointment to their partner that infected them with HIV.…”
Section: Discussionmentioning
confidence: 80%
“…These gender inequalities have stopped many women, including WLHIV, in middle and low-income countries, from achieving their right to a safe and enjoyable sexual life. 15,35 The interviews suggested women diagnosed over a long time and also involved in peer support activities demonstrated and reported higher levels of SRH literacy and confidence in negotiating their needs and rights. This indicates women's ability to negotiate SRH rights tends to be developed with community peer groups' support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The region is remote, with low population density, and has faced challenges with instability and terrorism [24]. Religious differences with the rest of the country may also influence attitudes and stigma towards HIV/AIDS [25]. The region has also experienced increasing infrastructure development over the past decade, including road construction, a new airport, and a new port, raising potential for evolving patterns of disease transmission as migration patterns change [26][27][28].…”
Section: Methodsmentioning
confidence: 99%